2013
DOI: 10.1021/jz302057m
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Conductance in a Series of Extended Viologen Molecules

Abstract: Single-molecule conductance in a series of extended viologen molecules was measured at room temperature using a gold-molecule-gold scanning tunneling microscopy break junction arrangement. Conductance values for individual molecules change from 4.8 ± 1.2 nS for the shortest compound to 2.9 ± 1.0 nS for the compound with six repeating units and length of 11 nm. The latter value is almost 3 orders of magnitude higher than that reported for all-carbon-based aromatic molecular wires of comparable length. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 82 publications
2
30
0
Order By: Relevance
“…For instance, for a series of oligophenyl methanethiols (C 6 H 5 CH 2 SH, C 6 H 5 C 6 H 4 CH 2 SH, and C 6 H 5 C 6 H 4 C 6 H 4 CH 2 SH), β was determined as 4.6 ± 0.7 nm −1 using the GaIn/Ga 2 O 3 eutectic contact technique on self-assembled monolayers of the molecules on template-stripped gold electrodes [35] (a similar value, 4.2 ± 0.7 nm −1 , was determined earlier using a conducting AFM technique [36]), while for a series of oligothiophenes with 5, 8, 11, and 14 2,5-coupled thiophene rings, β was 1 nm −1 , measured by the STM break junction method [21]. The lowest β values so far measured have been for extended viologens (0.06 nm −1 ) [37] and for conjugated fused oligoporphyrins, oligoporphyrin-ethynylene, and oligoporphyrinbutadiynylene systems, where values of 0.2-0.4 nm −1 have been found, the exact value depending on structure [24][25][26][27]. It should be noted that although a low value of β is often taken as an indication that the conductance mechanism could be hopping rather than superexchange (tunneling), it has been shown that the conductance behavior of even the most conjugated of these families of porphyrins as a function of temperature are still described well by theoretical models involving tunneling [24].…”
Section: -3supporting
confidence: 73%
“…For instance, for a series of oligophenyl methanethiols (C 6 H 5 CH 2 SH, C 6 H 5 C 6 H 4 CH 2 SH, and C 6 H 5 C 6 H 4 C 6 H 4 CH 2 SH), β was determined as 4.6 ± 0.7 nm −1 using the GaIn/Ga 2 O 3 eutectic contact technique on self-assembled monolayers of the molecules on template-stripped gold electrodes [35] (a similar value, 4.2 ± 0.7 nm −1 , was determined earlier using a conducting AFM technique [36]), while for a series of oligothiophenes with 5, 8, 11, and 14 2,5-coupled thiophene rings, β was 1 nm −1 , measured by the STM break junction method [21]. The lowest β values so far measured have been for extended viologens (0.06 nm −1 ) [37] and for conjugated fused oligoporphyrins, oligoporphyrin-ethynylene, and oligoporphyrinbutadiynylene systems, where values of 0.2-0.4 nm −1 have been found, the exact value depending on structure [24][25][26][27]. It should be noted that although a low value of β is often taken as an indication that the conductance mechanism could be hopping rather than superexchange (tunneling), it has been shown that the conductance behavior of even the most conjugated of these families of porphyrins as a function of temperature are still described well by theoretical models involving tunneling [24].…”
Section: -3supporting
confidence: 73%
“…The scanning tunneling microscopy break junction (STM‐BJ) technique was applied to investigate the charge transport through the tetraphenylmethane‐based molecular tripods. The STM‐BJ was formed repeatedly by perpendicular movement of the electrochemically etched gold tip (0.25 mm wire, 99.99 % Goodfellow, UK) toward the gold substrate immersed in a 1 m m solution of 7 or 21 in mesitylene, which was spiked with triethylamine to achieve in situ deprotection of the anchoring groups.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the molecular wire bridging the two metallic leads has a strong effect on the exponential attenuation factor β, as demonstrated by Wold et al in 2002. 14 Conjugated molecular wires such as oligophenylene exhibit conductance values that decay with increasing number of phenyl units to the extent of β = 0.41 Å −1 , and other conjugated systems such as oligophenyleneimine 15 and oligonaphthalenefluoreneimine 16 showed lower attenuation factors of 0.3 Å −1 and 0.25 Å −1 , respectively. Extremely low values of β were found in systems such as meso-to-meso bridged oligoporphyrins 13,17,18 (0.040 ± 0.006 Å −1 ), axially-bridged oligoporphyrins 19 (0.015 ± 0.006 Å −1 ), oligoynes 20 (0.06 ± 0.03 Å −1 ), carbodithioate-capped oligophenylene-ethynylene 4 (0.05 ± 0.01 Å −1 ), and extended viologens 21 (0.006 ± 0.004 Å −1 ). Oligothiophenes, on the other hand, showed a more complex behaviour, with unusual conductance decay with the number of thiophene rings [22][23][24] and, in the case of longer oligothiophenes with alkylthiol linkers, water-dependent conductance and conductance decay.…”
Section: Introductionmentioning
confidence: 99%